New insights into evolution of IgT genes coming from Antarctic teleosts - Giacomelli, Stefano; Buonocore, Francesco; Albanese, Fabio; Scapigliati, Giuseppe; Oreste, Umberto; Coscia, Maria Rosaria; GERDOL, MARCO (Marine Genomics, 2015)
Cloning and characterization of IgT heavy chain genes were performed in the Antarctic Notothenioid teleost Trematomus bernacchii and in a non-Antarctic Notothenioid species, Bovichtus diacanthus, belonging to a phyletically basal lineage of Notothenioids. Compared to IgT from other non-Antarctic teleost species, including B. diacanthus, T. bernacchii IgT lacked most of the second constant domain but maintained only a few amino acid residues, which could be aligned to B. diacanthus CH2 domain. By analyzing several cDNA clones from a single specimen, three differently sized IgT transcript variants, named Long, Short and Shortest, were identified. Genomic analysis of T. bernacchii and B. diacanthus IgH loci revealed that, in the case of T. bernacchii, within the intron between the exons coding for the entire first and second constant domains a reminiscence of the ancestral second exon was present. The Long and Short variants were found to be encoded by indel alleles, whereas the Shortest variant was generated by alternative splicing that led to the CH2 exonic remnant skipping. Through comparison between genomic and cDNA sequences we hypothesized the presence of three different copies of the IgT heavy chain gene, one of which being considered the functional gene since the corresponding transcripts were identified. Moreover, either Long or Short exonic variants were found to be used in IgT heavy chain membrane form in an unbiased manner, as seen for the secretory form. Phylogenetic analysis was performed on the constant region from all teleost IgT available to date, including IgT from another Antarctic Notothenioid species, Notothenia coriiceps, identified by searching the transcriptome. The loss of almost an entire domain together with the conservation of some amino acids such as proline, glycine and cysteine in the CH2 domain remnant, could be interpreted as another distinctive feature of the Antarctic fish genome evolution, providing also new insights into the structural variation of teleost immunoglobulin genes.